Simbolisme Anatomi Pohon dalam Al-Qur’an: Analisis Ekolinguistik dan Metafora Konseptual - Mustakim Saleh; Aliurridha Aliurridha; Jamaluddin Gesrianto A'ban (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study examines tree symbolism in QS Ibrahim, verses 24 and 26, by integrating ecolinguistic and conceptual metaphor approaches. It aims to reveal how the Qur’an employs tree metaphors to represent human morality and the resilience of faith. A descriptive-analytical qualitative method was used, involving observation and note-taking of the Qur’anic text, followed by mapping the concrete domain (tree anatomy) onto the abstract domain (moral concepts), and analysis using the Bang and Døør framework. Findings indicate that a good tree with strong roots, a sturdy trunk, and upward-reaching branches symbolizes a good statement, a foundation of faith, consistency of character, and growth of deeds. Conversely, a bad tree with uprooted roots and fragile structure represents a bad statement, moral instability, and a lack of foundational values. The conceptual model highlights the binary opposition of good and bad trees and underscores the role of human ecological experience in systematically understanding morality. These findings advance ecolinguistic and conceptual metaphor studies in Qur’anic linguistic research.